Probiotic viability of requeijão cremoso processed cheese formulations (Research, Society and Development, 2022)
The increased demand for foods that provide nutritional and health benefits increased research in probiotic microorganisms applied to dairy products. Probiotics are affected by several factors that decrease their action on the gastrointestinal system, making it vital to protect them using encapsulation techniques that allow their incorporation into various food products. The study herein aimed to evaluate the best way to incorporate Lactobacillus acidophilus (free and encapsulated) to Requeijão cremoso processed cheese varieties. The microorganism was applied to different curd formulations using green banana biomass as a partial fat substitute. The pH, probiotic viability during shelf life and throughout the simulated gastrointestinal conditions, and capsules produced were assessed. While applying free Lactobacillus acidophilus to Requeijão cremoso varieties proved functionally ineffective, the encapsulated formulations presented satisfactory probiotic counts in all treatments (8–10 log CFU g-1).